Metode Tahfidz Al-Qur’an Untuk Anak Usia Dini (Kajian Atas Buku Rahasia Sukses 3 Hafizh Quran Cilik Mengguncang Dunia) - Hidayah, Aida (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2018)
This article discusses methods of memorizing Qur’an for early childhood, as a form of early childhood education. The methods are very various. They are method of talqin, listening record of murottal, reading mushaf, motion and sign, etc. As one of the methods, the writer specifically talks about a way of memorizing qur’an for early childhood in a family of Kamil el-Laboody written on Rahasia Sukses 3 Hafizh Qur’an Cilik Mengguncang Dunia. He successfully educated his three children to be hafiz^ in their early childhood in 4,5 years old. Before entering the main idea, the writer elaborates how Islam (Qur’an and Hadis) and science talk about memorizing Qur’an for early childhood. Keywords: method, memorizing Qur’an, early childhood.